Wanderungsmotive zugewanderter älterer Menschen: Ein anderer Blick auf die Entwicklungsprobleme peripherer Räume in Brandenburg - Born, Karl Martin; Goltz, Elke; Saupe, Gabriele (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Rural peripheral areas in East Germany are often perceived as difficult regional cases for revitalisation; however, the problems in these regions are relatively neglected in comparison to the population decline or the degradation of accommodation in urban areas. In the context of regional development the aspects of the extent and motivation of elderly migrants into these areas are also marginalized. Although the current debates on the demographical change encompass rural areas as well the re-interpretation of the post-productivist life phase of the elderly and their impact on those areas deserves more attention. The paper presents the results from an enquiry amongst elderly migrants into the rural areas of Brandenburg and assesses their “potential” for rural development. Finally, the results from the enquiry lead to the consideration of necessary changes and improvements for spatial planning specifically aimed at the needs of the elderly.